Contextualizing Jewish temples - Ganzel, Ṭovah; Holtz, Shalom E. (The Brill reference library of ancient Judaism, 2021)
"Jewish temples stood in Jerusalem for nearly one thousand years and were a dominant feature in the life of the ancient Judeans throughout antiquity. This volume strives to obtain a diachronic and topical cross-section of central features of the varied aspects of the Jewish temples that stood in Jerusalem, one that draws on and incorporates different disciplinary and methodological viewpoints. Ten contributions are included in this volume by: Gary A. Anderson; Simeon Chavel; Avraham Faust; Paul M. Joyce; Yuval Levavi; Risa Levitt; Eyal Regev; Lawrence H. Schiffman; Jeffrey Stackert; Caroline Waerzeggers, edited by Tova Ganzel and Shalom E. Holtz"--